Glue solution for halogen-free antimony-free flame-retardant laminated board, prepreg, laminated board, preparation method and resin composition

By using specific resin compositions and preparation techniques, the shortcomings of existing laminates in terms of conductivity, heat resistance and flame retardancy are solved, and high-performance halogen-free antimony-free flame retardant laminates are achieved, meeting the high-performance needs of the electronic and electrical fields.

CN119875304APending Publication Date: 2025-04-25SHANGHAI GUOJI ELECTRONICS MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510250908.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing laminates such as CEM-3 or FR-4 have shortcomings in conductivity, heat resistance and flame retardancy, especially in terms of low conductivity, poor heat resistance and flame retardant systems often rely on halogen or antimony-containing compounds, which poses environmental and health threats.

Method used

Halogen-free and antimony-free flame retardant laminates are prepared by shear maturation and hot pressing vacuum compression techniques using a resin composition, including bisphenol A type epoxy resin, DOPO type modified phosphorus-containing epoxy resin, solid bisphenol A type epoxy resin, MDI-modified epoxy resin and linear bisphenol A formaldehyde resin.

Benefits of technology

The high thermal conductivity, good heat resistance and flame retardant properties of the laminate are achieved, which meets the demand for high-performance laminates in the electronic and electrical fields, while avoiding the use of toxic and harmful substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875304A_ABST
    Figure CN119875304A_ABST
Patent Text Reader

Abstract

The invention discloses a glue solution for a halogen-free antimony-free flame-retardant laminated board, a prepreg, a laminated board, a preparation method and a resin composition. The composition is prepared from the following components in parts by mass: 540 to 660 parts of bisphenol A epoxy resin, 900 to 1100 parts of DOPO (9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) modified phosphorus-containing epoxy resin, 360 to 440 parts of solid bisphenol A epoxy resin, 180 to 220 parts of MDI (methylenediphenyl diisocyanate) modified epoxy resin and 450 to 550 parts of linear bisphenol A formaldehyde resin. A flame-retardant laminated board (CEM-3) further prepared from a prepreg prepared from a glue solution of the composition has the advantages of high heat conductivity, no halogen and no antimony, and CTI is greater than or equal to 600 V, and TG is greater than or equal to 155 DEG C. The glue solution preparation method is simple, low in cost, stable in technology, low in reject ratio, high in process controllability and suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adhesive solution for a halogen-free and antimony-free flame-retardant laminate, a prepreg, a laminate and a preparation method and a resin composition. Background Art

[0002] In the field of electronics and electrical, as products develop rapidly towards miniaturization, high performance and high reliability, the requirements for basic materials such as laminates are becoming increasingly stringent.

[0003] Although traditional laminates CEM-3 or FR-4 are widely used, they still have the following problems: (1) Low conductivity: When electronic components are running at high power, heat is difficult to dissipate quickly, which can easily lead to local overheating, thereby affecting the stability and life of electronic equipment. (2) Poor heat resistance: Currently, laminates are developing towards high glass transition temperature (Tg). Laminates with medium-high Tg ("medium-high Tg" generally refers to Tg ≥ 140°C) can maintain good mechanical properties and dimensional stability in high temperature environments, avoiding deformation and warping due to temperature increases, which in turn affects the welding and assembly accuracy of electronic components. (3) Flame retardant systems often rely on halogen- or antimony-containing compounds. Halogen-containing flame retardants release a large amount of toxic and harmful gases, such as hydrogen bromide, when burned, which not only poses a serious threat to human health, but also causes serious secondary pollution in fire scenarios. Although antimony-containing compounds can synergistically flame retardant, the antimony element itself has certain biological toxicity, which is not conducive to long-term use from the perspective of environmental protection and sustainable development.

[0004] At present, there is an urgent need to develop laminates with excellent comprehensive properties, such as high thermal conductivity, good heat resistance, halogen-free and antimony-free flame retardancy. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the defect that CEM-3 or FR-4 lamination in the prior art cannot have excellent comprehensive performance, and provide a halogen-free and antimony-free flame-retardant laminate adhesive, prepreg, laminate and preparation method, resin composition. The adhesive in the present invention can achieve laminate TG ≥ 155 ° C, and further, it can also overcome the defects of low thermal conductivity of the pressboard in the prior art and the flame retardant system often relying on halogen or antimony compounds.

[0006] The present invention solves the above technical problems through the following technical solutions.

[0007] The present invention provides a resin composition, which comprises the following components in parts by mass:

[0008] 540-660 parts of bisphenol A epoxy resin, wherein the bisphenol A epoxy resin has an epoxy equivalent of 185-190 g / eq and a viscosity of 12000-15000 mPa·s at 25° C.;

[0009] 900-1100 parts of DOPO type modified phosphorus-containing epoxy resin, wherein the epoxy equivalent of the DOPO type modified phosphorus-containing epoxy resin is 295-335 g / eq;

[0010] 360-440 parts of solid bisphenol A epoxy resin, wherein the solid bisphenol A epoxy resin has an epoxy equivalent of 840-900 g / eq and a melt viscosity of 6000-9000 mPa·s at 150° C.;

[0011] 180-220 parts of MDI modified epoxy resin, wherein the epoxy equivalent of the MDI modified epoxy resin is 250-310 g / eq; and,

[0012] 450-550 parts of a linear bisphenol A formaldehyde resin, wherein the linear bisphenol A formaldehyde resin has a hydroxyl equivalent of 120-124 g / eq.

[0013] In some preferred embodiments, the mass fraction of the bisphenol A epoxy resin is 580 parts, 600 parts or 620 parts.

[0014] In some preferred embodiments, the bisphenol A epoxy resin may be NPEL128E produced by Kunshan Nan Ya.

[0015] In some preferred embodiments, the solid content of the bisphenol A epoxy resin may be 100%.

[0016] In some preferred embodiments, the mass fraction of the DOPO-type modified phosphorus-containing epoxy resin is 950 parts, 1000 parts or 1050 parts.

[0017] In some preferred embodiments, the DOPO-type modified phosphorus-containing epoxy resin may be DFE202 produced by Sichuan Dongcai.

[0018] In some preferred embodiments, the solid content of the DOPO-type modified phosphorus-containing epoxy resin may be 75%.

[0019] In some preferred embodiments, the phosphorus content of the DOPO-type modified phosphorus-containing epoxy resin may be 3.1-3.2%.

[0020] In some preferred embodiments, the mass fraction of the solid bisphenol A epoxy resin is 380 parts, 400 parts or 420 parts.

[0021] In some preferred embodiments, the solid bisphenol A epoxy resin may be medium molecular weight NPES-904H produced by Kunshan Nan Ya.

[0022] In some preferred embodiments, the 25° C. softening point of the solid bisphenol A epoxy resin may be 100-112.

[0023] In some preferred embodiments, the density of the solid bisphenol A epoxy resin at 25°C may be 1.18 g / cm 3 .

[0024] In some preferred embodiments, the mass fraction of the MDI-modified epoxy resin is 190 parts, 200 parts or 210 parts.

[0025] In some preferred embodiments, the MDI modified epoxy resin may be DFE205 produced by Sichuan Dongcai.

[0026] In some preferred embodiments, the solid content of the MDI modified epoxy resin may be 75%.

[0027] In some preferred embodiments, the weight percentage of the linear bisphenol A formaldehyde resin is 480 parts, 500 parts or 520 parts.

[0028] In some preferred embodiments, the linear bisphenol A formaldehyde resin may be SH-2130 produced by Shengquan Group.

[0029] In some preferred embodiments, the free bisphenol A content of the linear bisphenol A formaldehyde resin may be 13-17%.

[0030] In some preferred embodiments, the softening point of the linear bisphenol A formaldehyde resin may be 127-132°C.

[0031] In some preferred embodiments, the electrical conductivity of the linear bisphenol A formaldehyde resin may be ≤20 μs / cm.

[0032] In some preferred embodiments, the resin composition may be any one of the following three compositions:

[0033]

[0034] The above parts are all parts by mass.

[0035] The present invention also provides a raw material composition of a glue solution for a halogen-free and antimony-free flame-retardant laminate, which comprises the following components in parts by mass:

[0036] The resin composition as described above;

[0037] Solvents;

[0038] 72-88 parts of curing agent;

[0039] 0.9-1.1 parts of curing accelerator;

[0040] 18-22 parts of a silane coupling agent; and,

[0041] Inorganic filler.

[0042] In the present invention, the solvent may be any conventional solvent in the art that can dissolve the raw material composition.

[0043] In some preferred embodiments, the solvent includes a mixed solvent 1 and a mixed solvent 2, wherein the mixed solvent 1 is a solvent that can dissolve a curing agent, a curing accelerator and a portion of an inorganic filler, and the mixed solvent 2 is a solvent that can dissolve a coupling agent and a resin.

[0044] In some preferred embodiments, the mixed solvent 1 is a mixture of N,N-dimethylformamide DMF and other solvents to dissolve the curing agent (such as DICY) and the curing accelerator (such as imidazole), and the mixing ratio is adjusted to reduce the amount of DMF used.

[0045] In some preferred embodiments, the mixed solvent 1 includes DMF (N,N-dimethylformamide), ethanol, dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL). The mass ratio of DMF, ethanol, dimethyl sulfoxide, and γ-butyrolactone can be (4-6): (2-4): (0.8-1.2): 1, for example 5:3:1:1.

[0046] In the present invention, a mixed solvent 1 (for example, a mass ratio of 5:3:1:1) comprising DMF, ethanol, dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL) can ensure solubility while utilizing the volatility of ethanol to make the solvent system easier to remove during the drying process, thereby reducing the DMF content in the plate.

[0047] In some preferred embodiments, the mixed solvent 2 is a mixture of propylene glycol methyl ether (PM) and other solvents to dissolve the resin, and the mixing ratio is adjusted to reduce the amount of DMF used.

[0048] In some preferred embodiments, the mixed solvent 2 comprises propylene glycol methyl ether PM, ethyl acetate, and isopropanol, and the mass ratio of propylene glycol methyl ether PM, ethyl acetate, and isopropanol can be (4-6): (1-3): 2, for example 5:3:2.

[0049] In the present invention, the hydroxyl group and methoxy group of propylene glycol methyl ether PM in the mixed solvent 2 can form hydrogen bonds and other interactions with the polar part of the halogen-free resin, and the ester bond structure of ethyl acetate can generate affinity with similar ester bond structures in the resin. Isopropyl alcohol contains hydroxyl groups, and after mixing, it can enhance the dissolution effect on the hydroxyl-sensitive part of the halogen-free resin.

[0050] In some preferred embodiments, the mass fraction of the mixed solvent 1 is 450-550 parts, for example, 500 parts.

[0051] In some preferred embodiments, the mass fraction of the mixed solvent 2 is 765-935 parts, for example, 850 parts.

[0052] In some preferred embodiments, the mass fraction of the curing agent is 80 parts.

[0053] In some preferred embodiments, the curing agent is DICY (dicyandiamide).

[0054] In some preferred embodiments, the curing accelerator is diphenylimidazole.

[0055] In some preferred embodiments, the mass fraction of the curing accelerator is 0.95-1.05 parts, for example, 1.0 parts.

[0056] In some preferred embodiments, the silane coupling agent is KH-570, and its chemical name is γ-methacryloxypropyltrimethoxysilane.

[0057] In some preferred embodiments, the unsaturated double bonds in the molecular structure of the silane coupling agent can participate in free radical polymerization reactions and can be better combined with some resin systems containing unsaturated bonds. In the production of halogen-free copper clad laminates, the wettability and coating of the resin on inorganic fillers can be improved, and the dispersion of fillers in the resin can be enhanced, thereby improving the mechanical properties and electrical insulation properties of the copper clad laminates, and are particularly suitable for halogen-free copper clad laminates that require high water resistance and weather resistance.

[0058] In some preferred embodiments, the mass fraction of the silane coupling agent is 20 parts.

[0059] In some preferred embodiments, the amount of the inorganic filler may be 3150-3850 parts, for example 3500 parts.

[0060] In some preferred embodiments, the inorganic filler includes spherical magnesium hydroxide, silicon dioxide, talc and aluminum hydroxide.

[0061] In some preferred embodiments, the mass ratio of the spherical magnesium hydroxide, the silicon dioxide, the talc and the aluminum hydroxide may be (900-1100):(720-880):(450-550):(1080-1320), for example, 1000:800:500:1200, 900:720:450:1080 or 1100:880:550:1320.

[0062] In some preferred embodiments, the mass fraction of the magnesium hydroxide may be 900-1100 parts, for example, 1000 parts.

[0063] In some preferred embodiments, the purity of the magnesium hydroxide may be ≥95%, the whiteness may be ≥92; the particle size range may be D50, 4±1 μm; and the conductivity (10%, in water) may be 40 μs / cm.

[0064] In some preferred embodiments, the mass fraction of the silicon dioxide may be 720-880 parts, for example, 800 parts.

[0065] In some preferred embodiments, the purity of the silicon dioxide may be ≥99.5%, the whiteness may be ≥90, the particle size range may be D50, 5±1 μm; and the electrical conductivity may be (10%, in water): 40 μs / cm.

[0066] In some preferred embodiments, the mass fraction of the talc powder may be 450-550 parts, for example, 500 parts.

[0067] In some preferred embodiments, in the talc, SiO 2 The content can be 57-63, the MgO content can be 27-33, the whiteness can be ≥95, the particle size range D50 can be 3±1μm; the metal impurity content can be ≤0.025%.

[0068] In some preferred embodiments, the mass fraction of the aluminum hydroxide may be 1080-1320 parts, for example, 1200 parts.

[0069] In some preferred embodiments, the grade of the aluminum hydroxide is MARTINAL® OL-104LEO.

[0070] In some preferred embodiments, the purity of the aluminum hydroxide is ≥99.6%, and the whiteness is ≥93; the particle size range D50 can be 1.9±0.2μm; D90 can be 3.2±1.0μm; the oil absorption rate can be 27-32 ml / 100g; and the conductivity (10%, in water) can be 20μS / cm.

[0071] The aluminum hydroxide in the present invention can be used as a flame retardant to reduce the decomposition of the material surface and the formation of carbon particles, thereby significantly improving the flame retardancy of the material and reducing the thermal expansion coefficient and water absorption rate of the plate.

[0072] In some preferred embodiments, the composition of the raw material composition is shown in the following table:

[0073]

[0074] The above parts are all by mass.

[0075] The mixed solvent 1 is obtained by mixing N,N-dimethylformamide, ethanol, dimethyl sulfoxide and γ-butyrolactone in a mass ratio of 5:3:1:1;

[0076] The mixed solvent 2 is obtained by mixing propylene glycol methyl ether, ethyl acetate and isopropanol in a mass ratio of 5:3:2.

[0077] The present invention also provides a method for preparing a halogen-free and antimony-free flame-retardant adhesive for laminated boards, which comprises the following steps:

[0078] The components of the raw material composition as mentioned above are mixed, sheared and ripened to obtain the adhesive solution for the halogen-free and antimony-free flame-retardant laminated board.

[0079] In some preferred embodiments, the mixed solvent 1 (added according to each component), the curing agent (added according to each component) and the curing accelerator are mixed and stirred until dissolved to obtain a mixture A. The stirring time may be 10-12 hours.

[0080] In some preferred embodiments, the mixture A is mixed with the coupling agent, the resin (added according to each component), and the mixed solvent 2 (added according to each component) to obtain a mixture B. The stirring time may be 1-2 hours.

[0081] In some preferred embodiments, the mixture B and the inorganic filler (added according to each component) are mixed, sheared and ripened to obtain the adhesive for the halogen-free and antimony-free flame-retardant laminate.

[0082] In some preferred embodiments, the rotation speed of the shear ripening is 900-1600 rpm, such as 900-1100 rpm or 1500-1600 rpm.

[0083] In some preferred embodiments, the shear ripening temperature is 40-60°C, such as 45-50°C.

[0084] In some preferred embodiments, the shear ripening time is 18-22 hours.

[0085] In some preferred embodiments, the shear ripening process is:

[0086] First, shear aging is performed at a speed of 1400-1600 rpm and a glue temperature of 40-50°C for 5-7 hours, and then shear aging is performed at a speed of 900-1100 rpm and a glue temperature of 40-50°C for 13-15 hours (the total aging time is about 18-22 hours).

[0087] In some preferred embodiments, the method for preparing the adhesive for the halogen-free and antimony-free flame-retardant laminate comprises the following steps:

[0088] (1) Mix the mixed solvent 1 (added according to each component), the curing agent (added according to each component) and the curing accelerator, and stir until dissolved for 10-12 hours to obtain a mixture A;

[0089] (2) Mixing the mixture A with the coupling agent, the resin (added according to each component), and the mixed solvent 2 (added according to each component), and stirring for 1-2 hours to obtain a mixture B;

[0090] (3) Under stirring conditions, the mixture B and the inorganic filler (added according to each component) are mixed, and shear-ripened for 5-7 hours at a speed of 1400-1600 rpm and a glue temperature of 40-50° C., and then shear-ripened for 13-14 hours at a speed of 900-1100 rpm and a glue temperature of 45-50° C. (total aging time is about 18-22 hours), and finally the halogen-free and antimony-free flame-retardant laminate glue is obtained.

[0091] The present invention also provides a glue solution for halogen-free and antimony-free flame-retardant laminated boards, which is prepared by the above-mentioned preparation method.

[0092] The present invention also provides a method for preparing a prepreg for a halogen-free and antimony-free flame-retardant laminate, which comprises the following steps: coating the adhesive on a reinforcing material electronic-grade glass fiber felt, and drying to obtain the prepreg.

[0093] In the present invention, the electronic grade glass fiber mat is a prepreg raw material commonly used in the art. The electronic grade glass fiber mat is also called "E" glass fiber paper for printed circuit boards.

[0094] In the present invention, the electronic grade glass fiber felt can be EMP-75A1 or EMP-105A1 produced by Jiangsu Changhai.

[0095] In some preferred embodiments, in the method for preparing the prepreg for the halogen-free and antimony-free flame-retardant laminate (CEM-3), the coating equipment is a horizontal glue coating machine.

[0096] In the present invention, the coating vehicle speed may be 8-15 m / min, such as 12 m / min or 10 m / min.

[0097] In the present invention, preferably, the drying temperature is 200-240°C, such as 210°C or 220°C.

[0098] In the present invention, the temperature of the glue solution may be 30-45°C, for example 35°C.

[0099] In the present invention, the resin content of the prepreg can reach 80-90%, for example 85%.

[0100] In the present invention, the fluidity of the prepreg can reach 25-30%.

[0101] In the present invention, the volatile matter of the prepreg may be ≤0.5%.

[0102] The present invention also provides a prepreg for a halogen-free and antimony-free flame-retardant laminate, which is prepared by the method.

[0103] The present invention also provides a halogen-free and antimony-free flame-retardant laminate, which comprises at least one prepreg for the halogen-free and antimony-free flame-retardant laminate and a metal foil or a release film covering one or both sides of the laminated prepreg.

[0104] In the present invention, the laminated board may be a CEM-3 board. The CEM-3 board uses electronic grade glass fiber cloth (such as 7628, 2116, 1080) and electronic grade glass fiber mat (such as EMP-75A1 or EMP-105A1 produced by Jiangsu Changhai) as reinforcement materials.

[0105] The electronic grade glass cloth (alkali-free glass fiber cloth for printed circuit boards) or electronic grade glass fiber mat is a prepreg raw material commonly used in the art.

[0106] In some preferred embodiments, the metal foil is copper foil.

[0107] In some preferred embodiments, the halogen-free and antimony-free flame-retardant laminate has a thickness of 1.50-1.58 mm, such as 1.50 mm, 1.51 mm, 1.53 mm or 1.55 mm.

[0108] In some preferred embodiments, the comparative tracking index (CTI) of the halogen-free and antimony-free flame retardant laminate is ≥ 600 V, for example 600 V.

[0109] In some preferred embodiments, the thermal conductivity (thermal conductivity) of the halogen-free and antimony-free flame-retardant laminate is ≥ 1.0 W / mK, such as 1.41 W / mK, 1.43 W / mK or 1.51 W / mK.

[0110] In some preferred embodiments, the peel strength of the halogen-free and antimony-free flame-retardant laminate is ≥ 8.0 IBS / IN, such as 8.8 IBS / IN, 9.0 IBS / IN, 9.2 IBS / IN or 9.5 IBS / IN.

[0111] In some preferred embodiments, the bow / warping degree of the halogen-free and antimony-free flame retardant laminate is ≤1.0%, such as 0.1%, 0.3% or 0.2%.

[0112] In some preferred embodiments, the halogen-free and antimony-free flame-retardant laminate has no delamination and no blistering on the surface at 288° C. for 20 seconds.

[0113] In some preferred embodiments, the flame retardant grade of the halogen-free and antimony-free flame retardant laminate is UL94V0.

[0114] In some preferred embodiments, the glass transition temperature Tg of the halogen-free and antimony-free flame retardant laminate is ≥ 155°C, such as 155°C, 156°C, 157°C or 158°C.

[0115] In some preferred embodiments, the thermal decomposition temperature (Td) of the halogen-free and antimony-free flame-retardant laminate is ≥ 325°C, such as 335°C, 340°C, 338°C or 343°C.

[0116] In some preferred embodiments, the halogen-free and antimony-free flame-retardant laminate does not fade after being immersed in a process solvent for 60 minutes.

[0117] In some preferred embodiments, the halogen-free and antimony-free flame-retardant laminate does not turn yellow when baked at 200°C.

[0118] In some preferred embodiments, the antimony content of the halogen-free and antimony-free flame retardant laminate is 0 ppm.

[0119] In some preferred embodiments, the chlorine content of the halogen-free and antimony-free flame-retardant laminate is less than 900 PPM, such as 220 ppm, 210 ppm, 219 ppm or 223 ppm.

[0120] In some preferred embodiments, the bromine content of the halogen-free and antimony-free flame-retardant laminate is less than 900 PPM, such as 10 ppm, 15 ppm, 11 ppm or 12 ppm.

[0121] In some preferred embodiments, the total content of bromine and chlorine in the halogen-free and antimony-free flame-retardant laminate is less than 1500 PPM, such as 230 ppm, 225 ppm, 235 ppm or 228 ppm.

[0122] In some preferred embodiments, the laminate comprises, in sequence, a first copper foil layer, a semi-cured sheet whose reinforcing material is electronic-grade glass cloth 7628, two semi-cured sheets as described above (semi-cured sheets whose reinforcing material is electronic-grade glass fiber felt EMP-105A1), a semi-cured sheet whose reinforcing material is electronic-grade glass cloth 7628, and a second copper foil layer.

[0123] Among them, electronic grade glass cloth 7628 (purchased from Taishan Fiberglass, weight: 210g / m 2 ) The method for preparing a prepreg produced by the method may include the following steps:

[0124] Apply glue on electronic grade glass fiber cloth 7628 and then dry it. The coating equipment is a vertical glue machine, and the coating speed is 19m / min. The drying temperature is 210℃. The temperature of the glue is 40℃. The mass content of the resin in the semi-cured sheet can reach 50%. The gel time of the semi-cured sheet can reach 100-110s. The formula of the glue applied on the electronic grade glass fiber cloth 7628 is shown in the following table:

[0125]

[0126] Note: Mixed solvent A refers to: N,N-dimethylformamide DMF, ethanol, dimethyl sulfoxide DMSO, and γ-butyrolactone GBL mixed in a mass ratio of 5:3:1:1;

[0127] The mixed solvent B is obtained by mixing propylene glycol methyl ether PM, ethyl acetate EA and isopropanol in a mass ratio of 5:3:2.

[0128] The preparation method of coating glue on electronic grade glass fiber cloth 7628 may include the following steps:

[0129] ① Mix the mixed solvent A (added according to each component), curing agent (added according to each component), curing accelerator and flame retardant, and stir until dissolved for 10-12 hours to obtain mixture A;

[0130] ② Mix mixture A with coupling agent, resin (added according to each component), and mixed solvent B (added according to each component), and stir for 1-2 hours to obtain mixture B;

[0131] ③ Under stirring conditions, mix mixture B and inorganic filler (added according to each component), first shear and mature at a speed of 2200rpm and a glue temperature of 50℃ for 5 hours, then shear and mature at a speed of 1100rpm and a glue temperature of 50℃ for 7 hours (total aging time is about 12 hours), and finally obtain the electronic grade glass fiber cloth 7628 coated with glue.

[0132] In some preferred embodiments, the laminate comprises, in sequence, a first copper foil layer, a semi-cured sheet whose reinforcing material is electronic-grade glass cloth 2116, three semi-cured sheets as described above (semi-cured sheets whose reinforcing material is electronic-grade glass fiber felt EMP-75A1), a semi-cured sheet whose reinforcing material is electronic-grade glass cloth 2116, and a second copper foil layer.

[0133] Electronic grade glass cloth 2116 (purchased from Taishan Fiberglass, weight: 105g / m 2 ) The method for preparing a prepreg produced by the method may include the following steps:

[0134] Apply glue on electronic grade glass fiber cloth 2116 and then dry it. The coating equipment is a vertical glue coating machine, and the coating speed is 24m / min. The drying temperature is 220℃. The temperature of the glue is 40℃. The mass content of the resin in the semi-cured sheet can reach 55%. The gel time of the semi-cured sheet can reach 105-115s. The formula of the glue coating on electronic grade glass fiber cloth 2116 is the same as the glue coating on electronic grade glass fiber cloth 7628, and the preparation method of the glue coating on electronic grade glass fiber cloth 2116 is also the same as the glue coating on electronic grade glass fiber cloth 7628.

[0135] The present invention also provides a method for preparing the halogen-free and antimony-free flame-retardant laminate, which comprises the following steps:

[0136] (1) Lamination: Laminating a plurality of the halogen-free and antimony-free flame-retardant laminates with a prepreg, and covering the upper and lower surfaces with metal foil or release film to obtain a semi-finished plate;

[0137] (2) The semi-finished plate is subjected to hot pressing and vacuum pressing to obtain the semi-finished plate.

[0138] In the present invention, the preparation method of the semi-finished plate material can be: the semi-finished plate material is formed by a plurality of intermediate prepreg sheets, upper and lower copper foils / release films, upper and lower steel plates, and 18 upper and lower kraft papers.

[0139] In the present invention, no pressure is required when stacking, and the stacking requirements generally follow the four major principles in this field: the principle of matching high and low glue content, the principle of consistent layout, the principle of structural symmetry, and the principle of left and right matching.

[0140] In the present invention, different electronic glass fiber cloths or electronic glass fiber felts can be selected according to different thicknesses.

[0141] In step (2), the pressing method and conditions may be conventional methods and conditions in the art, such as hot pressing and vacuum staged pressing. Ensure that the sheet is cooled gradually to avoid direct pressure release after hot pressing, which may cause large internal stress in the sheet, and increase cold pressing to reduce sheet warping.

[0142] In the present invention, the vacuum value of the hot-pressing vacuum pressing may be 740-760 mmHg, preferably 750 mmHg.

[0143] In the present invention, the hot pressing and vacuum pressing can be carried out in stages, such as stage one, stage two, and stage three.

[0144] In the present invention, the first stage can be: the vacuum value is 740-760 mmHg, the temperature at the start of hot pressing is 110-130°C, and the pressure at the start of hot pressing is 4-6 kg / cm 2 The temperature at the end of hot pressing is 200-220℃, and the pressure at the end of hot pressing is 25-30 kg / cm 2 The hot pressing time is 50-60min.

[0145] In the present invention, the second stage can be: the vacuum value is 740-760 mmHg, the temperature of hot pressing is 200-220°C, and the pressure of hot pressing is divided into initial pressure, intermediate pressure and late pressure; the initial pressure is 25-30 kg / cm 2 The initial pressure pressing time is 10-15 min; the intermediate pressure is 35-40 kg / cm 2The mid-term pressure pressing time is 35-40 min; the late pressure is 20-25kg / cm 2 The time of the later pressure pressing is 10-15 min.

[0146] In the present invention, the third stage can be: vacuum or non-vacuum conditions, the temperature at the start of hot pressing is 200-220°C, and the pressure at the start of hot pressing is 20-25 kg / cm 2 The temperature at the end of hot pressing is 110-130℃, and the pressure at the end of hot pressing is 30-35kg / cm 2 The hot pressing time is 20-40min.

[0147] In the present invention, after the pressing, subsequent shape processing and inspection processes are generally performed to ensure the quality of the product.

[0148] In the present invention, the term “comparative tracking index” (CTI) is referred to as CTI for short.

[0149] In the present invention, the term “glass transition temperature” (TG) is abbreviated as TG.

[0150] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0151] The reagents and raw materials used in the present invention are commercially available.

[0152] The positive and progressive effects of the present invention are:

[0153] 1. The semi-cured sheet prepared by the adhesive of the present invention, and the flame-retardant laminate (such as CEM-3) further prepared have the advantages of high thermal conductivity, CTI ≥ 600 V, TG ≥ 155 ° C, and no halogen and no antimony. The preparation method of the adhesive in the present invention is simple, low in cost, stable in technology, low in defect rate, strong in process controllability, and suitable for mass production.

[0154] 2. The flame-retardant laminate (CEM-3) with high thermal conductivity, CTI ≥ 600 V, TG ≥ 155°C, halogen-free and antimony-free in the present invention meets the production process of the downstream printed circuit board (PCB) for the board, and has good comprehensive performance, especially halogen-free, thermal conductivity, CTI, flame retardant, TG, and thickness uniformity. For example, the bromine content (ppm) is less than 500ppm, which is far lower than the industry standard value (bromine content < 900ppm); the thermal conductivity is high. The flame-retardant laminate (CEM-3) with high thermal conductivity, CTI ≥ 600 V, TG ≥ 155°C, halogen-free and antimony-free in the present invention does not delaminate or bubble in the thermal stress test.

[0155] 3. The present invention adopts a combination of multiple resins, and selects resins with lower costs in the industry, such as bisphenol A epoxy resin (such as NPEL128 produced by Kunshan Nan Ya), which reduces costs while ensuring the performance of the board.

[0156] 4. Compared with the halogen-free FR-4 sheet, the halogen-free CEM-3 sheet of the present invention has better processing performance, is suitable for drilling, milling, and stamping processes, has better surface flatness, is lighter in weight, and has a lower price. BRIEF DESCRIPTION OF THE DRAWINGS

[0157] Figure 1 This is a schematic diagram of the structure of the laminate in Example 3 of the present invention. DETAILED DESCRIPTION

[0158] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0159] 1. In the following examples and comparative examples, the sources and descriptions of the raw materials are as follows:

[0160] DICY: dicyandiamide;

[0161] Diphenylimidazole: 2-Phenylimidazole;

[0162] Silane coupling agent KH-570: γ-methacryloxypropyltrimethoxysilane;

[0163] Bisphenol A epoxy resin: NPEL128E produced by Kunshan Nan Ya, solid content 100%, epoxy equivalent 185-190g / eq, viscosity 12000-15000mPa・s at 25℃;

[0164] DOPO-type modified phosphorus-containing epoxy resin: DFE202 produced by Sichuan Dongcai, with a solid content of 75%, epoxy equivalent of 295-335g / eq, and a phosphorus content of 3.1-3.2%;

[0165] The solid bisphenol A epoxy resin is medium molecular weight NPES-904H produced by Kunshan Nan Ya. Performance parameters: epoxy equivalent 840-900g / eq, softening point (25℃) 100-112, melt viscosity (150℃) 6000-9000mPa・s, density (25℃): 1.18 g / cm 3 .

[0166] The MDI modified epoxy resin is DFE205 produced by Sichuan Dongcai, with a solid content of 75% and an epoxy equivalent of 250-310.

[0167] Linear bisphenol A formaldehyde resin: SH-2130 produced by Shengquan Group, hydroxyl equivalent 120-124 g / eq, free bisphenol A 13-17%, softening point 127-132℃, conductivity ≤20μs / cm.

[0168] Magnesium hydroxide: purity ≥95%, whiteness ≥92, particle size range: D50, 4±1μm; conductivity (10%, in water): 40μs / cm.

[0169] Silicon dioxide: purity ≥99.5%, whiteness ≥90, particle size range: D50, 5±1μm; conductivity (10%, in water): 40μs / cm.

[0170] Talc: SiO 2 Content 57-63, MgO content 27-33, whiteness ≥95, particle size range: D50, 3±1μm; metal impurity content ≤0.025%.

[0171] Aluminum hydroxide: MARTINAL® OL-104LEO, purity ≥99.6%, whiteness ≥93, particle size range: D50, 1.9±0.2μm; D90, 3.2±1.0μm; oil absorption rate: 27-32 ml / 100g; conductivity (10%, in water): 20μs / cm;

[0172] DDS: 4,4'-diaminodiphenyl sulfone;

[0173] Graphene oxide: thickness is 0.8nm-1.2nm, single layer, specific surface area is 500m² / g-1000m² / g, carbon-oxygen ratio is between 2-4.

[0174] Bisphenol A novolac epoxy resin: SQAN-201EK80 produced by Shengquan, solid content 80%, epoxy equivalent 190-220g / eq;

[0175] Phenolic epoxy resin: DEN438 EK85J produced by Dow, solid content 85%, viscosity 600-1600mPa.s / 25℃, epoxy equivalent 176-181g / eq;

[0176] Bisphenol A type phosphorus-containing phenolic resin: XZ92741 produced by Dow, solid content 56-58%, viscosity 500-2500mPa.s / 25℃, phosphorus content 9-10%;

[0177] Tetrafunctional phenolic epoxy resin: NPPN431A70 produced by Kunshan Nan Ya, solid content 70%, epoxy equivalent 200-220g / eq, softening point: 82-92℃;

[0178] Spherical alumina: SLA-5, D50 particle size is 5±1μm, D90 particle size is 15±3μm.

[0179] 2. Effect data testing method:

[0180] Gel time test method:

[0181] (1) Crumble the resin of the prepreg into resin powder and place it on clean kraft paper.

[0182] (2) Collect the powder and place it through a 100-mesh sieve to sift out the fine powder, not less than 200 mg.

[0183] (3) Start the gel time tester and stabilize the temperature between the hot plates at 171±2℃.

[0184] (4) Clean the hot plate, use a small spoon to take 85~100 mg of powder and put it into the hot plate, and start the timer at the same time. When the gel system reaches 10 seconds, use a toothpick to stir it evenly. After a certain period of time, gently pull the sample. If the sample breaks, stop the timer. The timer reading at this time is the gel time.

[0185] Test method for resin fluidity:

[0186] (1) Cut four (4 ± 0.02) inch × (4 ± 0.02) inch square specimens on a square die punch. The specimens should be cut 3 mm away from the edge of the material.

[0187] (2) Use an electronic balance to weigh the total weight W1 of the four samples to an accuracy of 0.01g.

[0188] (3) Stack the four specimens neatly and sandwich them between two release films.

[0189] (4) The sandwich consisting of the sample, release film and steel plate is placed in a flow press to press the laminate.

[0190] (5) Pressing parameters are: temperature 171±5℃, pressure 0.45±0.03MPa, setting time 7min.

[0191] (6) Take out the pressed laminate and remove the release film.

[0192] (7) Use a round die punch to punch a disc with a diameter of 3.192 ± 0.02 inches in the center of the laminate.

[0193] (8) Use an electronic balance to weigh the disc, W2.

[0194] (9) Calculation: Fluidity (%) = [(W1-W2×2) / W1] × 100%.

[0195] Testing method for volatile matter content:

[0196] (1) On a square die punch, cut square specimens of (4 ± 0.02) inches × (4 ± 0.02) inches or (101.6 mm × 101.6 mm) (three pieces from the left, middle, and right sides of each specimen). Punch a small hole with a diameter of about 1 / 8 mm in the corner of the specimen. The specimen cannot be cut within 10 mm from the edge of the material.

[0197] (2) Weigh the sample to an accuracy of 0.001 g and record the weight W1.

[0198] (3) Use a paper clip to pass through the small hole of the sample and hang it under the shelf of the oven.

[0199] (4) Place the rack with the sample in an oven at 163±4℃ for 15±1min.

[0200] (5) Take the sample out of the oven and weigh it within 2 minutes to an accuracy of 0.001 g, and record the weight W2.

[0201] (6) Calculate the volatile matter content (%) = [(W1-W2) / W1] × 100%.

[0202] The detection method of comparative tracking index is: the highest voltage value that the material surface can withstand 50 drops of electrolyte without forming leakage traces.

[0203] The test method for thermal conductivity (thermal conductivity) is: ASTM D5470.

[0204] The test method for peel strength is: DIN 53273.

[0205] The method for detecting bow / warpage is to ensure that the four corners of the copper clad board are completely in contact with the plane. Then, measure the distance between the highest point in the middle and the plane. The calculation formula is: Warpage = (highest point distance / PCB board long side length) * 100%.

[0206] The testing method for glass transition temperature (Tg) is: E2 / 105 DSCIPC-TM-650 2.4.25.

[0207] The detection method of thermal decomposition temperature (Td) is: 10C / min, N, 5%WtLoss.

[0208] The test method for chemical resistance (process solvent immersion method) is: no fading for 60 minutes.

[0209] The test method for yellowing resistance (high temperature baking) is: ASTM D1729.

[0210] The detection method for antimony and halogen content is: IEC61249-2-21.

[0211] Example 1

[0212] Halogen-free and antimony-free flame-retardant laminate (CEM-3, in which PP (semi-cured sheet) produced by electronic glass fiber felt needs to use this glue) The raw material formula of the glue is as follows:

[0213] Table 1

[0214]

[0215] Note: Mixed solvent 1 refers to: N,N-dimethylformamide DMF, ethanol, dimethyl sulfoxide DMSO, and γ-butyrolactone GBL mixed in a mass ratio of 5:3:1:1;

[0216] The mixed solvent 2 is obtained by mixing propylene glycol methyl ether PM, ethyl acetate EA and isopropanol in a mass ratio of 5:3:2.

[0217] The preparation method of the adhesive for halogen-free and antimony-free flame-retardant laminate (CEM-3, in which the PP (semi-cured sheet) produced by electronic glass fiber felt needs to use this adhesive) specifically includes the following steps:

[0218] (1) Mix the mixed solvent 1 (added according to each component), the curing agent (added according to each component), and the curing accelerator, and stir until dissolved for 10-12 hours to obtain a mixture A;

[0219] (2) Mixing the mixture A with the coupling agent, the resin (added according to each component), and the mixed solvent 2 (added according to each component), and stirring for 1-2 hours to obtain a mixture B;

[0220] (3) Under stirring conditions, the mixture B and the inorganic filler (added according to each component) are mixed, and shear-ripened at a speed of 1500 rpm and a glue temperature of 45° C. for 6 hours, and then shear-ripened at a speed of 1000 rpm and a glue temperature of 45° C. for 14 hours (total aging time is about 20 hours), and finally, the glue for halogen-free and antimony-free flame-retardant electronic glass fiber felt is obtained.

[0221] Example 2

[0222] The present embodiment provides a method for preparing a prepreg for a halogen-free and antimony-free flame-retardant laminate (CEM-3), which comprises the following steps:

[0223] The electronic glass fiber felt is coated with the glue in Example 1 and then dried to obtain the electronic glass fiber felt.

[0224] Among them, the electronic glass fiber felt is a product type purchased from Jiangsu Changhai Electronic Glass Fiber Felt: EMP-75A1 or EMP-105A1 (alkali metal content is not more than 0.8%), and its parameter indicators are shown in the following table.

[0225] Table 2

[0226]

[0227] Among them, the specific parameters of the prepreg produced from electronic grade glass fiber mat are:

[0228] The coating equipment is a horizontal glue coating machine, and the coating speed is 10m / min. The drying temperature is 220℃. The temperature of the glue solution is 35℃. The mass content of the resin in the prepreg can reach 85%. The fluidity of the prepreg can reach 25~30%. The volatile matter of the prepreg is ≤0.5%.

[0229] Example 3

[0230] This embodiment provides a method for preparing a halogen-free and antimony-free flame-retardant laminate (CEM-3), which comprises the following steps:

[0231] (1) Lamination: 4 prepregs (1*7628+2*EMP-105A1+1*7628) are stacked and covered with copper foil on both the upper and lower surfaces to obtain a semi-finished plate. The semi-finished product is formed by 4 prepregs in the middle, upper and lower copper foils, upper and lower steel plates, and 18 pieces of kraft paper on the upper and lower surfaces;

[0232] Among them, the 4 stacked prepregs are: 1 prepreg produced by electronic grade glass cloth 7628 + 2 prepregs produced by electronic grade glass fiber felt EMP-105A1 prepared in Example 2 + 1 prepreg produced by electronic grade glass cloth 7628.

[0233] Electronic grade glass cloth 7628 (purchased from Taishan Fiberglass, weight: 210g / m 2 ) The method for preparing the prepreg produced comprises the following steps:

[0234] Apply glue on electronic grade glass fiber cloth 7628 and then dry it. The coating equipment is a vertical glue machine, and the coating speed is 19m / min. The drying temperature is 210℃. The temperature of the glue is 40℃. The mass content of the resin in the semi-cured sheet can reach 50%. The gel time of the semi-cured sheet can reach 100-110s. The formula of the glue applied on the electronic grade glass fiber cloth 7628 is shown in the following table:

[0235] Table 3 Raw material formula

[0236]

[0237] Note: Mixed solvent A refers to: N,N-dimethylformamide DMF, ethanol, dimethyl sulfoxide DMSO, and γ-butyrolactone GBL mixed in a mass ratio of 5:3:1:1;

[0238] The mixed solvent B is obtained by mixing propylene glycol methyl ether PM, ethyl acetate EA and isopropanol in a mass ratio of 5:3:2.

[0239] The preparation method of coating glue on electronic grade glass fiber cloth 7628 specifically includes the following steps:

[0240] ① Mix the mixed solvent A (added according to each component), curing agent (added according to each component), curing accelerator and flame retardant, and stir until dissolved for 10-12 hours to obtain mixture A;

[0241] ② Mix mixture A with coupling agent, resin (added according to each component), and mixed solvent B (added according to each component), and stir for 1-2 hours to obtain mixture B;

[0242] ③ Under stirring conditions, mix mixture B and inorganic filler (added according to each component), first shear and mature at a speed of 2200rpm and a glue temperature of 50℃ for 5 hours, then shear and mature at a speed of 1100rpm and a glue temperature of 50℃ for 7 hours (total aging time is about 12 hours), and finally obtain the electronic grade glass fiber cloth 7628 coated with glue.

[0243] (2) The semi-finished product is subjected to hot pressing and vacuum pressing to obtain a structure as shown in FIG. Figure 1 As shown. No pressure is required when laminating. Laminating requires the electronic glass fiber cloth PP to be on the outer layer and the electronic glass fiber felt to be in the core.

[0244] In step (2), the pressing method adopts hot pressing vacuum segmented pressing (the hot pressing vacuum value is 750 mmHg). Ensure that the plate is cooled gradually to avoid direct pressure release after hot pressing, which will cause large internal stress of the plate, and increase cold pressing to reduce plate warping.

[0245] Stage 1: Start to evacuate until the hot pressing vacuum value reaches 750 mmHg, and maintain it at 740-750 mmHg. Hot pressing temperature: 120-210℃ (this temperature range indicates a linear increase from 120℃ to 210℃), hot pressing pressure: 5-25 kg / cm 2 (This pressure range represents from 5 kg / cm 2 Linear pressure increase to 25 kg / cm 2 ), hot pressing time: 55min. The heating and pressure increase are completed during the entire pressing process, that is, the pressure increase and heating time is 55min, the starting temperature of the hot pressing is 120℃, and the hot pressing pressure is 5 kg / cm 2 The hot pressing end point temperature is 210℃ and the hot pressing pressure is 25 kg / cm 2 That is, the heating rate of hot pressing is 1.63℃ / min, and the pressure increase rate of hot pressing is 0.36 kg / cm 2 / min.

[0246] Stage 2: Continuously evacuate to ensure that the hot pressing vacuum value is 740-750 mmHg, hot pressing temperature: 210℃, hot pressing pressure is divided into initial pressure, mid-term pressure and late pressure, among which: initial pressure is 25kg / cm 2 , hot pressing time is 10min, medium pressure is 35kg / cm 2 The hot pressing time is 35 minutes, and the later pressure is 20 kg / cm 2 , Hot pressing time: 15min.

[0247] Stage 3: Stop vacuuming, hot pressing temperature: 210-120℃ (this temperature range represents a linear temperature drop from 210℃ to 120℃), hot pressing pressure: 20-30 kg / cm 2 (This pressure range represents from 20 kg / cm 2 Linear pressure increase to 30 kg / cm 2 ), hot pressing time: 30min. Cooling and pressing are completed during the whole pressing process, that is, the time of pressing and cooling is 30min, the starting temperature of hot pressing is 210℃, and the hot pressing pressure is 20 kg / cm 2 The hot pressing end point temperature is 120℃ and the hot pressing pressure is 30 kg / cm 2That is, the cooling rate of hot pressing is 3.00℃ / min, and the pressure increase rate of hot pressing is 0.33 kg / cm 2 / min.

[0248] Example 4

[0249] This embodiment provides a method for preparing a halogen-free and antimony-free flame-retardant laminate (CEM-3), which comprises the following steps:

[0250] (1) Lamination: 5 prepregs (1*2116+3*EMP-75A1+1*2116) are stacked and covered with copper foil on both sides to obtain a semi-finished plate. The semi-finished product is formed by 5 prepregs in the middle, upper and lower copper foils, upper and lower steel plates, and 18 pieces of kraft paper on the upper and lower sides;

[0251] Among them, the 5 stacked prepregs are: 1 prepreg produced from electronic grade glass cloth 2116 + 3 prepregs produced from electronic grade glass fiber felt EMP-75A1 prepared in Example 2 + 1 prepreg produced from electronic grade glass cloth 2116.

[0252] Electronic grade glass cloth 2116 (purchased from Taishan Fiberglass, weight: 105g / m 2 ) The method for preparing the prepreg produced comprises the following steps:

[0253] Apply glue on the electronic grade glass fiber cloth 2116, and then dry it. The coating equipment is a vertical glue coating machine, and the coating speed is 24m / min. The drying temperature is 220°C. The temperature of the glue is 40°C. The mass content of the resin in the semi-cured sheet can reach 55%. The gel time of the semi-cured sheet can reach 105-115s. The formula of the glue applied on the electronic grade glass fiber cloth 2116 is shown in the table of Example 3, and the preparation method of the glue is also the same as that of Example 3.

[0254] (2) The semi-finished product is subjected to hot-pressing and vacuum pressing to obtain the product. The operation and parameters of hot-pressing and vacuum pressing are the same as those in Example 3.

[0255] Embodiment 5-6

[0256] Example 5-6 Halogen-free and antimony-free flame-retardant laminate (CEM-3, where the PP (prepreg) produced by electronic glass fiber felt needs to use this glue) The glue formula raw material formula is as follows:

[0257] Table 4

[0258]

[0259] The mixed solvent 1 and the mixed solvent 2 are the same as those in Example 1. The preparation method of the prepreg for the halogen-free antimony-free flame retardant laminate (CEM-3) is the same as that in Example 2. The preparation method of the halogen-free antimony-free flame retardant laminate (CEM-3) is the same as that in Example 3.

[0260] Effect Example 1

[0261] The properties of the laminates obtained in Examples 3-6 were measured and the results are shown in Table 5.

[0262] Table 5 Performance parameters of laminated board in Examples 3-6

[0263]

[0264] Compared with the halogen-free FR-4 sheet, the halogen-free CEM-3 sheet of the present invention has better processing performance, is suitable for drilling, milling, and stamping processes, has better surface flatness, is lighter in weight, and has a lower price. Specifically,

[0265] The number of prepregs used is relatively small, which can be reduced by 50% compared to FR-4, which greatly improves production efficiency and reduces costs.

[0266] Drilling: The overall glass fiber content of halogen-free CEM-3 sheet is lower than that of halogen-free FR-4 sheet. During drilling, the wear on the drill bit is small, and the life of the drill bit blade is 2-5 times longer than that of drilling halogen-free FR-4 sheet, which can reduce processing costs and improve drilling efficiency.

[0267] Punching: Halogen-free CEM-3 sheets can punch out high-quality holes at room temperature, while halogen-free FR-4 sheets have poor punching processability. The dynamic shear stress of halogen-free CEM-3 sheets is 10%-15% lower than that of halogen-free FR-4 sheets, which reduces the wear on the punching die, and the punched shape is neat and complex, and there is no need to remove burrs.

[0268] V-groove processing: When the halogen-free CEM-3 plate is processed with a V-groove, the plate fracture is smooth without burrs, and the appearance quality after processing is good.

[0269] Better surface flatness: The texture of halogen-free CEM-3 sheet is very shallow, and the surface flatness is better than that of halogen-free FR-4 sheet. It is more suitable for surface mount technology (SMT), can provide a better foundation for the mounting of electronic components, and reduce the problem of poor mounting caused by uneven surface.

[0270] Lighter weight: The glass fiber content of halogen-free CEM-3 sheet is lower than that of halogen-free FR-4 sheet, so its weight is relatively lighter. In some electronic products with weight requirements, such as portable electronic equipment, aerospace electronic equipment, etc., it has certain advantages and can reduce the overall weight of the equipment.

[0271] Lower price: Generally speaking, the selling price of halogen-free CEM-3 sheets is about 18% lower than that of halogen-free FR-4 sheets. For cost-sensitive electronic product manufacturers, using halogen-free CEM-3 sheets can reduce raw material costs.

[0272] Comparative Example 1

[0273] Compared with the glue solution in Example 1, the formula of this comparative example is different only in the types of resin and inorganic filler, and the other formulas and conditions are the same as those in Example 1. Among them, the resin contains 600 parts of Kunshan Nan Ya NPEL128E bisphenol A epoxy resin, 1000 parts of Sichuan Dongcai DFE202DOPO modified phosphorus-containing epoxy resin and 400 parts of Kunshan Nan Ya NPES-904H solid bisphenol A epoxy resin. The inorganic filler contains 1000 parts of magnesium hydroxide and 1200 parts of aluminum hydroxide.

[0274] The preparation method of the prepreg for the halogen-free and antimony-free flame-retardant laminate (CEM-3) of this comparative example is the same as that of Example 2.

[0275] The preparation method of the halogen-free and antimony-free flame-retardant laminate (CEM-3) of this comparative example is the same as that of Example 3.

[0276] The performance of the laminated board of this comparative example was measured, and the results are shown in Table 6.

[0277] Table 6 Performance parameters of the laminate in Comparative Example 1

[0278]

[0279] Comparative Example 2

[0280] Compared with the glue solution in Example 1, the formula of this comparative example is different only in the types of resin and inorganic filler, and the other formulas and conditions are the same as those in Example 1. Among them, the resin contains 1000 parts of Sichuan Dongcai DFE202DOPO type modified phosphorus-containing epoxy resin, 200 parts of Sichuan Dongcai DFE205 MDI modified epoxy resin and 500 parts of Shengquan SH-2130 linear bisphenol A formaldehyde resin. The inorganic filler contains 800 parts of silicon dioxide and 1200 parts of aluminum hydroxide.

[0281] The preparation method of the prepreg for the halogen-free and antimony-free flame-retardant laminate (CEM-3) of this comparative example is the same as that of Example 2.

[0282] The preparation method of the halogen-free and antimony-free flame-retardant laminate (CEM-3) of this comparative example is the same as that of Example 3.

[0283] The performance of the laminated board of this comparative example was measured and the results are shown in Table 7.

[0284] Table 7 Performance parameters of the laminate in Comparative Example 2

[0285]

Claims

1. A resin composition, characterized in that By mass, it includes the following components: 540-660 parts of bisphenol A epoxy resin, wherein the bisphenol A epoxy resin has an epoxy equivalent of 185-190 g / eq and a viscosity of 12000-15000 mPa·s at 25° C.; 900-1100 parts of DOPO type modified phosphorus-containing epoxy resin, wherein the epoxy equivalent of the DOPO type modified phosphorus-containing epoxy resin is 295-335 g / eq; 360-440 parts of solid bisphenol A epoxy resin, wherein the solid bisphenol A epoxy resin has an epoxy equivalent of 840-900 g / eq and a melt viscosity of 6000-9000 mPa·s at 150° C.; 180-220 parts of MDI modified epoxy resin, wherein the epoxy equivalent of the MDI modified epoxy resin is 250-310 g / eq; and, 450-550 parts of a linear bisphenol A formaldehyde resin, wherein the linear bisphenol A formaldehyde resin has a hydroxyl equivalent of 120-124 g / eq.

2. The resin composition according to claim 1, characterized in that The resin composition satisfies one or more of the following conditions: (1) The mass fraction of the bisphenol A epoxy resin is 580 parts, 600 parts or 620 parts; (2) The bisphenol A epoxy resin is NPEL128E produced by Kunshan Nan Ya; (3) The solid content of the bisphenol A epoxy resin is 100%; (4) The mass fraction of the DOPO type modified phosphorus-containing epoxy resin is 950 parts, 1000 parts or 1050 parts; (5) The DOPO-type modified phosphorus-containing epoxy resin is DFE202 produced by Sichuan Dongcai; (6) The solid content of the DOPO type modified phosphorus-containing epoxy resin is 75%, and the phosphorus content is 3.1-3.2%; (7) The mass fraction of the solid bisphenol A epoxy resin is 380 parts, 400 parts or 420 parts; (8) The solid bisphenol A epoxy resin is NPES-904H produced by Kunshan Nan Ya; (9) The 25°C softening point of the solid bisphenol A epoxy resin is 100-112; (10) The density of the solid bisphenol A epoxy resin at 25°C is 1.18 g / cm 3 ; (11) The mass fraction of the MDI modified epoxy resin is 190 parts, 200 parts or 210 parts; (12) The MDI modified epoxy resin is DFE205 produced by Sichuan Dongcai; (13) The solid content of the MDI modified epoxy resin is 75%; (14) The weight percentage of the linear bisphenol A formaldehyde resin is 480 parts, 500 parts or 520 parts; (15) The linear bisphenol A formaldehyde resin is SH-2130 produced by Shengquan Group; (16) The free bisphenol A content of the linear bisphenol A formaldehyde resin is 13-17%; (17) The softening point of the linear bisphenol A formaldehyde resin is 127-132°C; and, (18) The electrical conductivity of the linear bisphenol A formaldehyde resin is ≤20 μs / cm.

3. A raw material composition of glue, characterized in that: The invention comprises the following components by weight: the resin composition as claimed in claim 1 or 2, 72-88 parts of a curing agent, 0.9-1.1 parts of a curing accelerator, 18-22 parts of a silane coupling agent, a solvent and an inorganic filler.

4. The raw material composition of the glue solution according to claim 3, characterized in that: The raw material composition of the glue solution meets one or more of the following conditions: (1) The solvent includes a mixed solvent 1 and a mixed solvent 2, wherein the mixed solvent 1 includes N,N-dimethylformamide, ethanol, dimethyl sulfoxide and γ-butyrolactone, and the mixed solvent 2 includes propylene glycol methyl ether, ethyl acetate and isopropanol. Among them, in the mixed solvent 1, the mass ratio of N,N-dimethylformamide, ethanol, dimethyl sulfoxide and γ-butyrolactone is preferably (4-6): (2-4): (0.8-1.2): 1, for example, 5:3:1:1; the mass fraction of the mixed solvent 1 is preferably 450-550 parts, for example, 500 parts; in the mixed solvent 2, the mass ratio of propylene glycol methyl ether, ethyl acetate and isopropanol is preferably (4-6): (1-3): 2, for example, 5:3:2; the mass fraction of the mixed solvent 2 is preferably 765-935 parts, for example, 850 parts; (2) The mass fraction of the curing agent is 80 parts; (3) The curing agent is dicyandiamide; (4) The curing accelerator is diphenylimidazole; (5) The mass fraction of the curing accelerator is 0.95-1.05 parts, for example, 1.0 parts; (6) The silane coupling agent is KH-570; (7) The mass fraction of the silane coupling agent is 20 parts; (8) the amount of the inorganic filler is 3150-3850 parts, for example 3500 parts; and, (9) The inorganic filler includes spherical magnesium hydroxide, silicon dioxide, talc and aluminum hydroxide; The mass ratio of the spherical magnesium hydroxide, the silicon dioxide, the talc and the aluminum hydroxide is preferably (900-1100): (720-880): (450-550): (1080-1320), for example, 1000: 800: 500: 1200, 900: 720: 450: 1080 or 1100: 880: 550: 1320; The mass fraction of the magnesium hydroxide is preferably 900-1100 parts, for example 1000 parts; the mass fraction of the silicon dioxide is preferably 720-880 parts, for example 800 parts; the mass fraction of the talc is preferably 450-550 parts, for example 500 parts; the mass fraction of the aluminum hydroxide is preferably 1080-1320 parts, for example 1200 parts.

5. A method for preparing a glue solution, characterized in that: The method comprises the following steps: mixing the components of the raw material composition of the glue solution as claimed in claim 3 or 4, shearing and ripening, and obtaining the glue solution; Preferably, the rotation speed of the shear ripening is 900-1600 rpm, such as 900-1100 rpm or 1500-1600 rpm; Preferably, the shear ripening temperature is 40-60°C, such as 45-50°C; Preferably, the shearing and ripening time is 18-22 hours; Preferably, the shear aging process is: firstly shear aging at a speed of 1400-1600 rpm and a glue temperature of 40-50° C. for 5-7 hours, and then shear aging at a speed of 900-1100 rpm and a glue temperature of 40-50° C. for 13-15 hours.

6. A glue solution, characterized in that: The glue is prepared by the method for preparing the glue as claimed in claim 5.

7. A method for preparing a prepreg for a halogen-free and antimony-free flame-retardant laminate, characterized in that: The method comprises the following steps: coating the adhesive solution as claimed in claim 6 on the electronic grade glass fiber felt as a reinforcing material, and drying the adhesive solution; Preferably, the electronic grade glass fiber mat is EMP-75A1 or EMP-105A1 produced by Jiangsu Changhai; Preferably, the coating equipment is a horizontal gluing machine; Preferably, the coating vehicle speed is 8-15 m / min, such as 12 m / min or 10 m / min; Preferably, the drying temperature is 200-240°C, for example 210°C or 220°C; Preferably, the temperature of the glue solution is 30-45°C, for example 35°C; Preferably, the resin content of the prepreg is 80-90%, for example 85%; Preferably, the fluidity of the prepreg can reach 25-30%; Preferably, the volatile matter of the prepreg may be ≤0.5%.

8. A prepreg for a halogen-free and antimony-free flame-retardant laminate, characterized in that: The semi-cured sheet is prepared by the method for preparing the halogen-free and antimony-free flame-retardant laminate according to claim 7.

9. A halogen-free and antimony-free flame-retardant laminate, characterized in that: It comprises at least one prepreg for halogen-free and antimony-free flame-retardant laminated board as claimed in claim 8 and a metal foil or a release film covering one side or both sides of the laminated prepreg; Preferably, the laminate comprises in sequence a first copper foil layer, a prepreg whose reinforcing material is electronic grade glass cloth 7628, two prepregs for halogen-free antimony-free flame retardant laminates as claimed in claim 8, a prepreg whose reinforcing material is electronic grade glass cloth 7628, and a second copper foil layer, wherein the reinforcing material of the prepreg for halogen-free antimony-free flame retardant laminate is electronic grade glass fiber mat EMP-105A1; The method for preparing the semi-cured sheet produced by electronic grade glass cloth 7628 preferably comprises the following steps: coating glue on the electronic grade glass fiber cloth 7628, and then drying to obtain the semi-cured sheet; wherein the coating equipment is preferably a vertical glue coating machine, and the formula of the glue coated on the electronic grade glass fiber cloth 7628 is preferably as shown in the following table: ; The mixed solvent A is obtained by mixing N,N-dimethylformamide, ethanol, dimethyl sulfoxide and γ-butyrolactone in a mass ratio of 5:3:1:1; the mixed solvent B is obtained by mixing propylene glycol methyl ether, ethyl acetate and isopropanol in a mass ratio of 5:3:2; Preferably, the laminate comprises in sequence a first copper foil layer, a prepreg whose reinforcing material is electronic grade glass cloth 2116, three prepregs for halogen-free antimony-free flame retardant laminates as claimed in claim 8, a prepreg whose reinforcing material is electronic grade glass cloth 2116, and a second copper foil layer; the reinforcing material of the prepreg for halogen-free antimony-free flame retardant laminate is electronic grade glass fiber mat EMP-75A1; Among them, the preparation method of the semi-cured sheet produced by electronic-grade glass cloth 2116 preferably includes the following steps: coating glue on the electronic-grade glass fiber cloth 2116, and then drying to obtain; wherein, the equipment used for coating is preferably a vertical gluing machine; the formula of the glue coated on the electronic-grade glass fiber cloth 2116 is preferably the same as the glue coated on the electronic-grade glass fiber cloth 7628.

10. A method for preparing the halogen-free and antimony-free flame-retardant laminate according to claim 9, characterized in that: It includes the following steps: (1) Lamination: Laminating a plurality of the halogen-free and antimony-free flame-retardant laminates with a prepreg, and covering the upper and lower surfaces with metal foil or release film to obtain a semi-finished plate; (2) hot-pressing and vacuum-pressing the semi-finished plate to obtain; In step (2), the vacuum value of the hot-pressing vacuum pressing is preferably 740-760 mmHg, more preferably 750 mmHg; In step (2), the pressing method is preferably hot-pressing vacuum segmented pressing; the hot-pressing vacuum pressing is preferably carried out in stages, including stage one, stage two, and stage three; The first stage is preferably: the vacuum value is 740-760 mmHg, the temperature at the start of hot pressing is 110-130°C, and the pressure at the start of hot pressing is 4-6 kg / cm 2 The temperature at the end of hot pressing is 200-220℃, and the pressure at the end of hot pressing is 25-30 kg / cm 2 , the hot pressing time is 50-60min; The second stage is preferably: the vacuum value is 740-760 mmHg, the temperature of hot pressing is 200-220°C, and the pressure of hot pressing is divided into initial pressure, intermediate pressure and late pressure; the initial pressure is 25-30 kg / cm 2 The initial pressure pressing time is 10-15 min; the intermediate pressure is 35-40 kg / cm 2 The mid-term pressure pressing time is 35-40 min; the late pressure is 20-25kg / cm 2 The time of the late pressure pressing is 10-15 min; The third stage is preferably: vacuum or non-vacuum conditions, the temperature at the start of hot pressing is 200-220°C, and the pressure at the start of hot pressing is 20-25 kg / cm 2 The temperature at the end of hot pressing is 110-130℃, and the pressure at the end of hot pressing is 30-35kg / cm 2 The hot pressing time is 20-40min.